Improving the Quality of Human Resources in Developing the Performance of the State Civil Apparatus - R. Taqwaty Firdausijah (SEAN Institute, 2022)
When it comes to ASN's ability to perform out their assigned tasks and responsibilities in a professional and efficient manner, a high-quality human resources department is widely regarded as a critical aspect. The purpose of this study is to investigate the initiatives that have been taken to enhance the level of human resources (HR) in order to boost the efficiency of the state civil apparatus (ASN). This investigation was carried out in Compreng District, which is located in Subang Regency, by making use of a qualitative approach and the method of case study. For the purpose of this investigation, data was gathered by conducting in-depth interviews with ASNs who play a role in the management and development of human resources within important government institutions. In addition, document analysis and observations were carried out in order to acquire a full comprehension of the current circumstance. According to the findings of this research, enhancing the quality of human resources in the process of developing ASN performance in the Compreng sub-district can be accomplished through the provision of general orientation, the facilitation of employee needs, the socialization of technical instructions, the provision of opportunities to increase employee capabilities in academic improvement, and the involvement of technical guidance and employee training.